1999
DOI: 10.1159/000010062
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Determination of Several Serum Tumor Markers in Patients with Primary Epithelial Ovarian Carcinoma

Abstract: This study was designed to evaluate the clinical significance of the use of preoperative serum tumor markers in primary epithelial ovarian cancer. Subjects comprised 111 patients with primary epithelial ovarian cancer. Lactate dehydrogenase (LDH), α-hydroxybutyrate dehydrogenase (HBDH), carcinoembryonic antigen (CEA), CA19-9, tissue polypeptide antigen (TPA), CA125 and sialyl TN (STN) serum levels were measured within 7 days before surgery. The tumor marker values were compared with the histopathologic diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 9 publications
1
27
2
Order By: Relevance
“…In our study, we found 40% of ovarian mucinous carcinomas to be associated with an elevated serum CA19.9 level. This is at variance with other studies that have reported an elevated CA19.9 level in between 76.9% and 83.3% of ovarian mucinous carcinomas 5 13. These latter studies included larger numbers of mucinous carcinoma than our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we found 40% of ovarian mucinous carcinomas to be associated with an elevated serum CA19.9 level. This is at variance with other studies that have reported an elevated CA19.9 level in between 76.9% and 83.3% of ovarian mucinous carcinomas 5 13. These latter studies included larger numbers of mucinous carcinoma than our study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in the current study the serum STN level was not a prognostic factor for the survival of colorectal cancer patients after surgery. We are not aware of any report that has described the prognostic value of preoperative serum STN levels in colorectal cancer patients, although the prognostic value for patients with gastric cancer and ovarian cancer has been reported [40][41][42]. The incidence of high serum STN levels in the colorectal cancer patients in the present study was lower than that in patients with gastric (13-28%) or ovarian cancer (50.0-63.2%) [40][41][42].…”
Section: Discussioncontrasting
confidence: 60%
“…We are not aware of any report that has described the prognostic value of preoperative serum STN levels in colorectal cancer patients, although the prognostic value for patients with gastric cancer and ovarian cancer has been reported [40][41][42]. The incidence of high serum STN levels in the colorectal cancer patients in the present study was lower than that in patients with gastric (13-28%) or ovarian cancer (50.0-63.2%) [40][41][42]. Therefore, serum STN levels need to be determined in a larger number of colorectal cancer patients to clarify the prognostic value of this carbohydrate antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found that serum concentrations of TPA correlated with length of survival in lung, prostate, colorectal, and bladder cancer [21,[35][36][37]. However, other authors observed that elevated serum concentrations of TPA were not associated with a worse prognosis in colorectal, ovarian, endometrial, and cervical cancer [24,[38][39][40]. Overall, the prognostic value of serum concentrations of TPA has been discussed controversially.…”
Section: Discussionmentioning
confidence: 99%